(untitled) (Scientific journal of the Fergana State University, 2026)
During 2021-2024, as a result of our research work in various territories of Karakalpakstan, helminths belonging to 34 species were found in sheep. For the first time in the CIS, it was noted that of these species, Fasciola gigantica parasitizes not only the liver of sheep, but also their lungs, and 13 species of helminths were also registered for the first time in Karakalpakstan. It was noted that 34 species of helminths parasitizing sheep belong to 24 genera, 15 families, 9 orders, 3 classes and 2 types of the animal world. It became known that the largest number of identified species of helminths, or more precisely, 24 species belong to the class of nematodes (70.6%), 7 species - to the class of cestodes (20.6%) and 3 species - to the class of trematodes (8.8%), it also turned out that out of 34 species of helminths, 21 species (61.8%) are geohelminths and 13 species (38.2%) - biohelminths.